Determination of storage capacity and command area in a small reservoir irrigation system - Misra, Deo Narain; Goto, Akira; Loof, Rainer; Murty, V.V.N.; Paudyal, Guna N.; Government of Federal Republic of Germany (Bangkok : Asian Institute of Technology, 1989)
Small reservoirs are used in irrigation systems which have small command areas and can be implemented with small budget. A small reservoir "Begnas Tal" for Begnas Irrigation Project, Pokhara, Nepal, is chosen for this study. A combined model for rainfall-runoff relationships, crop water requirements, supplementary irrigation demand and inflow - outflow of reservoir is developed. "Automatic Calibration of Tank Model " developed by SUGAWARA is applied to calibrate the outlet coefficients of tank model for rainfall runoff relationships. The combined model is used to analyse the relationships between annual inflow, reservoir storage capacity, command area and cropping pattern. The results of the above analysis are used to design the optimal storage capacity of the reservoir for given command area and then, at this capacity, an assessment for area allocation for paddy and wheat in dry season along with paddy in rainy season is carried out.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1989
Keywords: Water-storage; Reservoirs